A Study on Psychological Anxiety and Employability in the Context of Department Store Beauty Advisors amidst Consumer Purchasing Behavior Change in the New Normal Era: Focusing on Mediating the Effect of Cognitive Flexibility - Park, Su Mi; Han, Hye Ree (Asian Journal of Beauty and Cosmetology, 2025)
Purpose: The research aims to investigate how changes in customer purchasing behavior and the resulting psychological anxiety of beauty advisors affect their employability in the new normal era following COVID-19. Additionally, it seeks to understand the mediating role of cognitive flexibility in this relationship.Methods: To accomplish this, a questionnaire survey was administered to 600 department store beauty advisors between June 20 and July 20, 2023, and data from 555 were collected. To ensure the validity of the study, a research model was tested, using SPSS WIN 25.0. This study investigated whether psychological anxiety and changes in consumers' purchasing behavior affected department store beauty advisors' employability and etc.Results: The findings reveal that psychological anxiety significantly affect the employability of department store beauty advisors. Cognitive flexibility plays a mediating role, suggesting that higher cognitive flexibility can mitigate the negative impacts of changing consumer behaviors on employability.Conclusion: The study concludes that enhancing cognitive flexibility among beauty advisors can help them better adapt to the new normal environment, thereby improving their employability. Cosmetic businesses can leverage these insights to develop strategies that enhance their employees' cognitive flexibility and responsiveness to changing consumer behaviors and etc.